RESPONSE OF FINISHER BROILER CHICKENS TO DIETARY LEVELS OF BAUCHI RED SORGHUM VARIETY - Doma, U. D.; Adamu, N.; Jama’a, N. A.; Mubarakat, Y. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This experiment was conducted to determine the response of finisher broiler chickens to dietary replacement levels of Bauchi Red Sorghum (BRS) for maize. Five experimental diets were formulated in which BRS replaced maize at 0, 25, 50, 75 and 100% levels, coded as diets A, B, C, D and E, respectively. Two hundred (200) broiler chickens weighing between 1147.50 and 1180.00g were allotted to the five diets in replicates of two containing 20 birds each in a Complete Randomized Design. Feed and water were served ad libitum and the study lasted for 21 days. Data for growth performance indices (feed intake, body weight gain, feed conversion ratio, feed efficiency, survivability) and cost benefit (feed cost, feed cost per kg gain and cost saving) were collected. Results showed that total weight gain was higher (P<0.05) on diet E (1052.50g) which was similar to diet B (1027.50g), diet C (1014.00g) and diet D (1005.00g) than on diet A (995.00g). The daily weight gain also followed the same trend with significantly (P<0.05) higher value on diet E (50.12g), which was similar to the values observed on diet B (48.93g), diet C (48.29g) and diet D (47.86g) while the lowest value of 46.43g was obtained on diet A (control diet). Similarly, feed conversion ratio was also better in broiler birds fed diets C and E (2.74) whereas the poorest feed conversion ratio of 2.97 was found on diet A. Feed cost (N/kg) declined progressively from N500.00 on diet A to N380.00 for diet E. Similarly, feed cost per kg gain also decreased from N1474.49 on diet A to N1038.57 on diet E. Consequently, the highest percent cost saving was realized on diet E. It is therefore concluded that Bauchi red sorghum variety can completely replace maize in the diets of finisher broiler chickens with improved performance and better cost benefits.